THE INFLUENCE OF PROFITABILITY, LEVERAGE AND ACTIVITY ON THE SHARE PRICE WITH LIQUIDITY RATIO AS MODERATING VARIABLE - Kawijaya, Jovita Zefanya Stephanie; Simorangkir, Enda Noviyanti; Tarigan, Aremi Evanta (Universitas Jember, 2024)
ABSTRACTStock prices can be predicted using financial ratios. Researchers in this study only examined Profitability, Activity, Leverage, and Liquidity ratios. This research examines and analyzes stock prices on companies on the ISE or Indonesia Stock Exchange with Tbk status, 2019 – 2022. The variables tested are profitability, activity, and leverage, using liquidity as a moderating variable. The quantity intended selection was relating to using a purposive sampling method with historical data acquired from IDX website, www.idx.co.id. The data analysis process was related to using PLS Algorithm calculations on SmartPLS to exercise the hypothesis. The research results cause that profitability and activity have a significant bring on stock prices, while leverage is not significant result on share prices. Apart from that, the moderating variable of liquidity only has a significant bring on share prices as an independent variable because, with its position as a moderating variable, liquidity does not significantly result to the profitability, activity, and leverage variables. The effect of research provides sufficient insight that share prices generally have a greater influence on investor behavior.Keywords: Profitability; Activity; Leverage; Share Price; Liquidity ABSTRAKHarga saham dapat diprediksi dengan menggunakan rasio keuangan. Peneliti dalam penelitian ini hanya meneliti rasio Profitabilitas, Aktivitas, Leverage, dan Likuiditas. Penelitian ini menguji dan menganalisis harga saham pada perusahaan di BEI atau Bursa Efek Indonesia yang berstatus Tbk, tahun 2019 – 2022. Variabel yang diuji adalah profitabilitas, aktivitas, dan leverage, dengan menggunakan likuiditas sebagai variabel moderasi. Pemilihan kuantitas yang dimaksud adalah dengan menggunakan metode purposive sampling dengan data historis diperoleh dari website IDX, www.idx.co.id. Proses analisis data terkait dengan penggunaan perhitungan Algoritma PLS pada SmartPLS untuk menguji hipotesis. Hasil penelitian menunjukkan bahwa profitabilitas dan aktivitas berpengaruh signifikan terhadap harga saham, sedangkan leverage tidak berpengaruh signifikan terhadap harga saham. Selain itu, variabel moderasi likuiditas hanya mempunyai pengaruh yang signifikan terhadap harga saham sebagai variabel independen karena dengan posisinya sebagai variabel moderasi, likuiditas tidak berpengaruh signifikan terhadap variabel profitabilitas, aktivitas, dan leverage. Pengaruh penelitian memberikan wawasan yang cukup bahwa harga saham secara umum mempunyai pengaruh yang lebih besar terhadap perilaku investor..Kata Kunci: Profitabilitas; Aktivitas; Leverage; Harga Saham; Likuiditas